Comparing ways of calculation efficiency of regenerative heat exchanger - A. A. Serov; A. V. Tsygankov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This article contains information on various methods for calculating the efficiency of regenerative heat exchangers in an air ventilation system. The equations of heat balance and heat transfer are described. The results obtained on the CFD model are compared with the results obtained by various mathematical calculations. The obtained results of the computational study can give an assessment of the accuracy of computational methods to obtain the value of the efficiency of regenerative heat exchangers.